The effectiveness of online agricultural extension in bekasi regency - Fadhlurrahman, Iqbal; Sadono, Dwi; Fatchiya, Anna (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2024)
The current development of ICT is transforming the approach to agricultural extension from conventional methods to advanced method by incorporating digital technology. Jarkomluhdes is an online agricultural extension activity implemented as an effort to enhance the institutional development of extension services at the village level, known as Posluhdes. This research aims to analyze the level of participation and effectiveness of Jarkomluhdes, as well as to examine the influencing factors. The study employs a quantitative approach and survey method. The population includes 132 officials and members of Posluhdes spread across 12 villages in 5 sub-districts of Bekasi Regency, with a census sampling method. Data is analyzed using PLS method through SmartPLS 3.2.9. The level of participation and effectiveness of Jarkomluhdes is categorized as very low. The role of facilitators and the availability of facilities and infrastructure influence the level of participation. Furthermore, the level of participation affects the effectiveness of Jarkomluhdes.